Diagnostical value of urgent laparoscopy.: Nuestra experiencia en 1000 casos - Negrotto, Gonzalo; Trostchansky, José (Cirugía del Uruguay, 1987)
Urgent laparoscopy is a quíck examination, of practi• caily no risks, and of high effectiveness. In our expe• rience, in 97.7% of multi-traumatized and 91.5% of non traumatic acute abdomen, urgent laparoscopy mak'es the operation of patients whose injuries are not clini• caily or paraclinicaily evident possible In "useful time". What is more, it prevents a great number of useless la• parotomies.